2023
DOI: 10.3389/fpsyg.2023.1113654
|View full text |Cite
|
Sign up to set email alerts
|

Instruction effects on randomness in sequence generation

Abstract: Randomness is a fundamental property of human behavior. It occurs both in the form of intrinsic random variability, say when repetitions of a task yield slightly different behavioral outcomes, or in the form of explicit randomness, say when a person tries to avoid being predicted in a game of rock, paper and scissors. Randomness has frequently been studied using random sequence generation tasks (RSG). A key finding has been that humans are poor at deliberately producing random behavior. At the same time, it ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 113 publications
(166 reference statements)
1
13
0
Order By: Relevance
“…In a recent study we confirmed that randomization performance depends on the precise instructions (Guseva et al, 2023). In that experiment, the requirement to choose randomly was explicitly stated in some instruction conditions ("choose randomly") while being more indirectly implied in others.…”
Section: Task Diversity In Rsg Studiessupporting
confidence: 63%
See 4 more Smart Citations
“…In a recent study we confirmed that randomization performance depends on the precise instructions (Guseva et al, 2023). In that experiment, the requirement to choose randomly was explicitly stated in some instruction conditions ("choose randomly") while being more indirectly implied in others.…”
Section: Task Diversity In Rsg Studiessupporting
confidence: 63%
“…As in our previous behavioral study (Guseva et al, 2023), we studied the neural effects of different randomization task instructions in a between-subjects design to avoid carry-overs between tasks. Each participant received one of the three task instructions: Explicit Randomness (ER), Free Choice (FC) and Mental Coin Toss (MC).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations